Case Report: A Well-Hidden Cause for Myelopathy - Braun, Tobias; Schulz, Eva; Viard, Maxime; AlhajOmar, Omar; Struffert, Tobias; Gattenloehner, Stefan; Yeniguen, Mesut; Juenemann, Martin (Frontiers in Neurology, 2021)
Introduction: Sarcoidosis is a rare, systemic inflammatory disease and can involve multiple organs, especially the lungs and lymph nodes. The nervous system is affected in <10 percent of patients, which is called neurosarcoidosis. Neurosarcoidosis can cause a multitude of symptoms and can mimic various diseases. A rare manifestation is bone marrow involvement. We describe a case of spinal cord syndrome due to myelopathy that was caused by sarcoidosis of the bone marrow. Case Presentation: A male patient presented to our hospital with incomplete spinal cord syndrome. He suffered from numbness of the legs which had progressed to severe paraparesis. Magnetic resonance imaging revealed thoracic myelopathy without contrast enhancement. Thorough diagnostics found no explanation for the myelopathy, and the patient was treated symptomatically with high-dose steroids. When the patient developed non-resolving leukopenia, a bone marrow biopsy was performed. The bone marrow showed changes due to sarcoidosis. Further testing revealed myocardial involvement of the sarcoidosis. The patient was started on oral prednisolone and methotrexate. Over the course of time, his symptoms improved, but he still suffers from spastic leg paresis and needs aids to walk farther than 1 kilometre. Conclusion: In patients presenting with neurological deficits of unknown cause, neurosarcoidosis is a potential explanation. If it manifests primarily in the bone marrow, the diagnosis can be easily overlooked. Abnormalities in a full blood count should make the treating physician consider this diagnosis, and a bone marrow biopsy should be performed.